Improving Energy Efficiency for Culinary MSMEs in Legok Village Through Electrical Management Training - Marojahan Tampubolon; Fahmy Rinanda Saputri; Melissa Indah Fianty (I-Com: Indonesian Community Journal, 2024)
This community service aims to empower Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Legok Village, Tangerang, Banten through efficient electrical management training and the implementation of an energy consumption monitoring system. Legok Village, known for its diverse traditional culinary offerings, faces challenges in managing efficient electricity consumption in their daily operations. It is known that in the culinary field, various electrical appliances are needed to support the preparation of food and beverages. The use of these electrical devices needs to be closely monitored so that their management can be regulated to become more energy-efficient. This service includes practical training and education on energy-saving practices, efficient electrical equipment, and power management strategies to help culinary MSMEs in Legok Village reduce electricity costs and enhance the sustainability of their businesses.